2009
DOI: 10.1002/ppap.200800199
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Model Proteins Using Beams of Argon Ions, Oxygen Atoms and Molecules: Mimicking the Action of Low‐Pressure Ar/O2 ICP Discharges

Abstract: The action of Ar/O2 plasmas with proteins is mimicked by employing a particle beam experiment with individually controllable and absolutely calibrated sources of O atoms/O2 molecules and of argon ions. It is demonstrated that beams of thermal O atoms and of O2 molecules with fluences up to jO = 8.6 × 1018 cm−2 and jO2 = 5.4 × 1020 cm−2 have no measurable effect on the proteins at room temperature, whereas the combination of an O/O2 beam and of an 100 eV Ar+ ion beam induces very efficient protein removal, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…[56] It has been demonstrated that neither H atoms nor O atoms alone have the capability to cause significant erosion of the treated biological systems at room temperature as demonstrated by 2D ellipsometric D-angle maps of protein samples (untreated and after exposure to O and H beams for 60 min in Figure 7) and by SEM images of B. atrophaeus spores exposed to an O-atom beam for 60 min (Figure 8 b).…”
Section: Wwwchemphyschemorgmentioning
confidence: 97%
“…[56] It has been demonstrated that neither H atoms nor O atoms alone have the capability to cause significant erosion of the treated biological systems at room temperature as demonstrated by 2D ellipsometric D-angle maps of protein samples (untreated and after exposure to O and H beams for 60 min in Figure 7) and by SEM images of B. atrophaeus spores exposed to an O-atom beam for 60 min (Figure 8 b).…”
Section: Wwwchemphyschemorgmentioning
confidence: 97%
“…A large number of plasma sources and biological targets have been investigated to date and there is growing amount of literature that suggests that for low-temperature atmospheric-pressure plasmas the interaction with biological targets is mainly chemistry driven [3,4,5]. UV radiation and physical etching observed in low-pressure plasma treatments [6,7] do not seem to play a dominant role at atmospheric pressure. Indeed the flux of neutral ROS to the target is orders of magnitude larger than that of ions and at atmospheric pressure the ion energy is generally small due to the large collisionality of the sheaths [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical sputtering was already proven to be a solid framework for sterilization and biomolecules etching data interpretation [27,[42][43][44]. Plasma characterization described in the previous section provides a dataset for reactive particle fluxes, which are proportional to the bulk densities of radical atoms and molecules as measured by actinometry.…”
Section: Role Of the Radicalsmentioning
confidence: 99%